A modified randomized device for estimation of population mean of quantitative sensitive variable with measure of privacy protection. Issue 4 (3rd April 2022) - Singh, Garib Nath; Singh, Chandraketu; Kumar, Amod
Abstract: This work presents a randomization device for the estimation of population mean related to quantitative sensitive characteristics using blank card strategy. Measure of privacy protection for the proposed randomized response models have been described. The proposed technique provides the unbiased estimation procedures of population mean along with enhanced privacy protection of the respondents. Empirical studies are performed to support the theoretical results and efficiency of the models are also verified by suggesting an unified measure which show the dominance of the proposed models over existing models. Results are analyzed and suitable recommendations are put forward to the survey practitioners.